PENGARUH SUSTAINABILITY REPORT PADA REAKSI PASAR DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL KONTROL - Wijaya, Made Surya; Sudana, I Putu (E-Jurnal Akuntansi, 2017)
The purpose of this study is to determine the effect of intensity of disclosure within sustainability reporting  to market reaction which are represented by stock return and trading volume activity with two control variabel added wich are return on assets and debt to equity ratio. This study used a sample of 48 companies from thrree years observation of 2014-2016. The examination of hypothesis are conducted using multilinear regression technique. This study conclude that intensity of disclosure within sustainability reporting has no effect on stock return yet has positive effect on trading volume activity. Return on assets as control variabel has positive effect on stock return and trading volume activity. Debt to equity ratio as control variabel has no effect on stock return and trading volume activity. The way market reacts toward sustainability reporting such as has no significant effect on stock return yet has positive effect on trading volume activity indicate there is mixed perception phenomenon amongst the investors. Keywords: sustainability report, stock return, trading volume activity, debt to equity ratio, return on          assets.